Attributes motivating participation in extreme recreation at Putrajaya Challenge Park, Malaysia - Che Ibrahim, Nur Syuhada; Mohammad Afandi, Syamsul Herman; Samdin, Zaiton (Forestry Department Peninsular Malaysia, 2013)
Extreme recreation refers to activities in relation to height, speed, physical exertion and generally involving a certain level of danger. The Putrajaya Challenge Park (PCP) is a recreational complex that provides opportunity for extreme recreation emphasising on wall climbing, skateboarding/rollerblading, mountain biking and bicycle motor cross. Since motivation is a significant factor of extreme recreation participation, it is essential for the management of PCP to understand extreme recreation participants' motivation. This study was conducted to determine the motivation that influenced the public to participate in extreme recreation, particularly the existing activities of PCP. A survey was conducted on the participants of PCP for two months to obtain a total of 198 questionnaires. A multiple linear regression analysis was employed to identify the attribute towards extreme sport involvement. Regression analysis found that five factors were significant at 95% confidence level which included travelling time, skill and knowledge of participant, age, years of education and monthly income. Skill and knowledge, age and years of education were directly proportional to participation rate. Meanwhile, travelling time and monthly income were found to be inversely related to participation rate.